Pengembangan Bahan Ajar Biologi Berbasis Humor Materi Pencemaran Lingkungan Pada SMP Kelas VII - Rahman, Fathur; Nurhayati, B, Nurhayati, B; Rachmawaty, Rachmawaty (Universitas Negeri Makassar, 2019)
Abstract. The purpose of this study is to develop humor-based teaching materials on environmental pollution material for class VII students who are valid and practical. This type of research is development research (R & D). The development of this magazine uses the ADDIE model. The ADDIE stage is analysis, design, development, implementation and evaluation. This magazine's evaluation was evaluated by two expert validators. The results of the evaluation of biological humor comics by expert validators show that the biology humor comics are valid with a value of 4.49 (valid). The practicality of the product obtained from the teacher's response with a value of 83% (practical) and the response of students with a value of 81% (practical). Based on these results, it can be concluded that the development of biological humor comics in environmental pollution material is valid and practical. Keywords: comics, humor, teaching materials